Eye safety awareness and visual impairment prevention for computer users - Elena Serea; Codrin Donciu (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2022)
The paper presents an etiologic approach to visual and ocular alterations caused by intensive computer usage, with the aim of carrying out the risk factors and presenting the preventive measures that are to be applied. The prevalence of computer-induced eye problems is constantly growing and will remain so as long as humanity is dependent on most activities on electronic devices. The eye care burden is exclusively in charge of the user and the multitude of intrinsic, environmental, professional, and ergonomic factors with specific preventive measures are quite difficult to manage. In more developed communities there is an emphasis on eye health education, periodic ophthalmological examinations, and ergonomic organization of the computer workspace, but an important subjective risk factor remains nevertheless uncontrolled: the proximity to the screen during work. For this matter, it is presented one solution for visual impairment prevention among computer users, consisting of a simple automated system (OptoGuard) for warning persons when working too close to the screen, exceeding the eye safety proximity interval (which is measured through the webcam). The preliminary results, obtained for the Euclidean distance measurement, as the webcam currently allows, had an average error of 4%, the warning message appearing on the screen every time the user's proximity fell below 38 cm. Further developments aim at expanding the visual area monitoring to asses several levels of the other factors that lead to computer-related health problems: posture, angle of viewing, and brightness of the screen.